DETERMINASI PEMBERDAYAAN PEKERJA MIGRAN INDONESIA DI MALAYSIA: PERAN MANAJEMEN SDM, STRATEGI PEMASARAN, DAN LITERASI KEUANGAN - Hernita Hernita; Iwan Perwira; Arfiany Arfiany; Nur Hidayah; Fismayatni Cholifah (Journal Economic Management and Business, 2026)
This study aims to analyze the determinants of Indonesian migrant workers’ empowerment in Malaysia through the roles of human resource management, marketing strategy, and financial literacy. A quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) was applied. Data were collected through questionnaires from 112 Indonesian migrant workers in Malaysia using purposive sampling. The findings reveal that human resource management, marketing strategy, and financial literacy positively and significantly influence migrant workers’ empowerment. Financial literacy emerged as the most dominant factor in improving economic independence, followed by human resource management and marketing strategy. The coefficient of determination indicates that the model has strong explanatory power for the empowerment variable. These results suggest that strengthening financial management capability, supported by effective HR practices and marketing skills, can encourage migrant workers to become independent economic actors. This study contributes theoretically and provides practical insights for sustainable empowerment policies.